Worker Participation in Decision‐making, Worker Sorting, and Firm Performance. Issue 4 (6th August 2021) - Mueller, Steffen; Neuschaeffer, Georg
Abstract : Worker participation in decision‐making is often associated with high‐wage and high‐productivity firm strategies. Using linked employer–employee data for Germany and worker fixed effects from a two‐way fixed‐effects model of wages capturing observed and unobserved worker quality, we find that plants with formal worker participation via works councils indeed employ higher quality workers. We show that worker quality is already higher in plants before council introduction and further increases after the introduction. Importantly, we corroborate previous studies by showing positive productivity and profitability effects even after taking into account worker sorting.